Evidence of microbiome contribution to the escalation of pyrethroid resistance in the major malaria vectors Anopheles gambiae s.s. and Anopheles funestus s.s - Fleuriane Metissa Djondji Kamga; Leon M. Jean Mugenzi; Vanessa Brigitte Ngannang-Fezeu; François Sougal Ngambia Freitas; Calmes Ursain Bouaka Tsakeng; Maurice Marcel Sandeu; Magellan Tchouakui; Charles Sinclair Wondji (BMC Microbiology)
Abstract Background Exacerbation of pyrethroid resistance severely jeopardises the effectiveness of malaria vector control efforts. However, the mechanisms enabling the vectors to now survive exposure to very high doses of pyrethroids remain unclear. Here, using High-throughput sequencing of the 16 S ribosomal RNA gene coupled with antibiotic treatment, we provide evidence linking the mosquito microbiome to the escalation of pyrethroid resistance in major African malaria vectors, Anopheles gambiae (s.s.) and Anopheles funestus (s.s.). Results Phenotypic characterisation of An. gambiae (s.s.) and An. funestus (s.s.) populations revealed a high level of resistance to pyrethroid in both species, with mortality rates < 91% at 10x the diagnostic dose of each insecticide. A significant difference in bacterial composition was observed in An. gambiae s.s. between resistant mosquitoes exposed to 1X and 10X the diagnostic dose of permethrin, and the susceptible strains (PERMANOVA-F: 8.06; p = 0.02). The abundance of Pseudomonas_1 (Log2FC: 4.42, p = 0.0001) and Burkholderia_1 (Log2FC: 4.95, p = 0.001) bacteria were consistently associated with mosquitoes surviving 1X and 10X the diagnostic concentrations of permethrin, respectively, while Serratia_2 bacteria was mostly associated with insecticide susceptibility. In the An. funestus s.s. strain, there was no significant difference in bacterial alpha- and beta-diversity between the FUMOZ-R (exhibiting normal deltamethrin resistance) and FUMOZ-HR (selected for high deltamethrin resistance), suggesting a minimal impact of selection pressure on bacterial composition. However, in FUMOZ-HR, there was an increase in the abundance of Rahnella (Log2FC: 15.954, p = 9.73 E-12) and Leucobacter (Log2FC: 7.6, p = 0.008) bacteria, indicating their potential role in worsening deltamethrin resistance. Furthermore, treating resistant mosquitoes (both Anopheles species) with broad-spectrum bactericidal antibiotics (penicillin/streptomycin) via sugar solution increased their susceptibility to various diagnostic doses of permethrin and deltamethrin in WHO pyrethroid intensity bioassays. Conclusion Overall, our study emphasises the potential role of the microbiome in the escalation of insecticide resistance in Anopheles mosquitoes, identifying key bacterial strains associated with insecticide resistance and susceptibility. These candidate bacteria warrant further investigation to elucidate the mechanisms by which they contribute to the escalation of pyrethroid resistance.